2009
DOI: 10.1029/2008rs004001
|View full text |Cite
|
Sign up to set email alerts
|

Vertical and oblique ionospheric soundings over a very long multihop HF radio link from polar to midlatitudes: Results and relationships

Abstract: [1] A vertical incidence sounder (VIS) was installed at the Spanish Antarctic Base (62.7°S, 299.6°E) during the Antarctic summer survey [2004][2005]. In addition, an oblique sounding (OS) system for HF communications between Antarctica and Spain (12,700 km) has been operated during the Antarctic summers since December 2003. OS results are compared to Rec533 model and to VIS data obtained from stations located along the radio path, including VIS stations at the emitter and receiver sites. The results presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 12 publications
1
26
0
Order By: Relevance
“…This HF radio link was used as multi-hop Oblique Ionospheric Sounder, OIS. In [57], Vilella et al have shown that the frequencies with largest availability of the HF radio link (FLA) correlate reasonably well with the MUF(3000)F2 recorded by VIS placed at the receiver site (40.8°N, 0.5°E) (see Figure 10, left) and that frequencies of OIS delivered at the receiver being larger than the MUF(3000)F2 recorded by VIS suffer a significant drop of power. The left plot of Figure 9 also shows the maximum usable frequency obtained by the Rec 533 model (MUF Rec 533) which is defined as the highest frequency for which an ionospheric communication path is predicted on 50% of the days of the month [58].…”
Section: Vertical Ionospheric Soundingmentioning
confidence: 74%
See 1 more Smart Citation
“…This HF radio link was used as multi-hop Oblique Ionospheric Sounder, OIS. In [57], Vilella et al have shown that the frequencies with largest availability of the HF radio link (FLA) correlate reasonably well with the MUF(3000)F2 recorded by VIS placed at the receiver site (40.8°N, 0.5°E) (see Figure 10, left) and that frequencies of OIS delivered at the receiver being larger than the MUF(3000)F2 recorded by VIS suffer a significant drop of power. The left plot of Figure 9 also shows the maximum usable frequency obtained by the Rec 533 model (MUF Rec 533) which is defined as the highest frequency for which an ionospheric communication path is predicted on 50% of the days of the month [58].…”
Section: Vertical Ionospheric Soundingmentioning
confidence: 74%
“…The significant decrease of the foF2 and their strong uplift of the F2 layer as observed by the significant increase in the virtual height, h'F2, for the geomagnetically disturbed period of 18 February 2005, was also investigated and explained in terms of a response of the ionosphere to the geomagnetic storms [55,56]. In addition, the data recorded with the AIS VIS, especially MUF(3000)F2, have been correlated with data extracted from the HF radio link established between the ASJI and Spain [57]. This HF radio link was used as multi-hop Oblique Ionospheric Sounder, OIS.…”
Section: Vertical Ionospheric Soundingmentioning
confidence: 99%
“…The behavior of the channel is well-known, as a result of several research studies (Vilella et al, 2009;, thus the control performance can be manually adjusted, by means of the acquisition system knowledge.…”
Section: Fuzzy Logic As An Acquisition Controlmentioning
confidence: 99%
“…They are absolutely based on analysis of real data (Vilella et al, 2009;, except for scenario 0, that is a simpler version of transmissions throughout ionospheric radiolink, considering only the most powerful path in a multipath scenario. Table 1 is sorted by h l , that is the hour time -during day or night -.…”
Section: Scenario Descriptionmentioning
confidence: 99%
See 1 more Smart Citation